Interpolative best proximity point results via $ γ $-contraction with applications - Müzeyyen Sangurlu Sezen (AIMS Mathematics, 2025)
In this paper, we introduce a $ ρ $-interpolative Kannan and Ćirić-Reich-Rus type fuzzy proximal contraction using a $ γ $-contraction. We prove some best proximity theorems of this new approximation using the concept of $ ρ $-proximal admissibility in complete fuzzy metric spaces. We generalize some previous studies and present fixed point results of the best proximity theorems in complete fuzzy metric spaces. Also, we extend some best proximity results to the partially ordered fuzzy metric spaces.